Peran Standar Nasional Pendidikan dalam Mewujudkan Sistem Pendidikan yang Berkualitas dan Merata - Intan Zahra Kamila; Dian Eka Puspiatasari; Sabrina Salsabila (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to examine the role of National Education Standards (SNP) in realizing a quality and equitable education system in Indonesia. The method used is descriptive qualitative with a literature study approach to various scientific sources discussing the implementation of SNP, including educator professionalism, education management, and quality equity between regions. The results of the study show that the SNP functions as the main instrument for quality assurance as well as a strategy for educational equity through eight standards that must be met by each educational unit. The implementation of the SNP has been proven to improve the quality of learning, the competence of educators, and the accountability of school management. In addition, the SNP plays a role in narrowing the gap in educational quality between regions by establishing uniform performance indicators at the national level. However, implementation in the field still faces obstacles in the form of limited human resources, infrastructure, and uneven policy support. Therefore, collaboration among stakeholders is needed to optimize the implementation of the SNP through continuous training, managerial supervision, and strengthening of the internal quality assurance system in schools. This study confirms that the SNP is a strategic foundation for building a quality, inclusive, and equitable national education system in the era of educational transformation.